2022
DOI: 10.1084/jem.20220829
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency for SAMHD1 activates MDA5 in a cGAS/STING-dependent manner

Abstract: Defects in nucleic acid metabolizing enzymes can lead to spontaneous but selective activation of either cGAS/STING or RIG-like receptor (RLR) signaling, causing type I interferon–driven inflammatory diseases. In these pathophysiological conditions, activation of the DNA sensor cGAS and IFN production are linked to spontaneous DNA damage. Physiological, or tonic, IFN signaling on the other hand is essential to functionally prime nucleic acid sensing pathways. Here, we show that low-level chronic DNA damage in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…Indeed, in agreement with our data, SAMHD1-deficiency and subsequent accumulation of endogenous RNA substrates is a cause of type I interferonopathies, characterized by an upregulation of distinct IFN-stimulated genes (ISGs) ( 20 , 24 ). Moreover, it has also been shown that chronic interferon response in SAMHD1-KO mice was driven by the MDA5 pathway in close concordance with our data in ovarian cancer cells ( 25 ) and further supporting the idea that SAMHD1 depletion is able to enhance innate immune activation and inflammation in cancer cells, a process that might have an important impact on ovarian cancer clinical outcome. In view of the promising pre-clinical data, we evaluated the role of SAMHD1 in 22 ovarian cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in agreement with our data, SAMHD1-deficiency and subsequent accumulation of endogenous RNA substrates is a cause of type I interferonopathies, characterized by an upregulation of distinct IFN-stimulated genes (ISGs) ( 20 , 24 ). Moreover, it has also been shown that chronic interferon response in SAMHD1-KO mice was driven by the MDA5 pathway in close concordance with our data in ovarian cancer cells ( 25 ) and further supporting the idea that SAMHD1 depletion is able to enhance innate immune activation and inflammation in cancer cells, a process that might have an important impact on ovarian cancer clinical outcome. In view of the promising pre-clinical data, we evaluated the role of SAMHD1 in 22 ovarian cancer patients.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in long-lived bats, continuous presence of multiple viruses could trigger a TLR7/STING-induced activation of a p16 program in immune cells and tissue protection against both infection and tissue damage 66 . At the same time, significantly reduced DNA-sensing in bats could keep STING activation in its low and physiological or, as also referred to, "tonic" state 67 while preventing a strong pro-inflammatory response that could be detrimental for disease tolerance (Figures 4F&G). In another long-lived animal, the naked mole-rat, a lack of response to Poly (I:C) reported in hematopoietic stem cells may suggest a strong attenuation of MDA5-dependent sensing 68 .…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical standpoint, we found that p16-expressing immune subsets were significantly reduced in the blood of severe COVID-19 patients further supporting their critical role in preventing lethal inflammation. The clinical efficacy of the BNT162b2 mRNA vaccine in reducing the risk of hospitalization was demonstrated as early as 10 days after the first dose when the specific immune response has not yet been established 66 in terms of development of specific antibodies 67 and the cellular responses 68 . Our results could explain these early benefits of vaccination on the risk of hospitalization by temporarily inducing p16 high immune cell-dependent disease tolerance that would eventually limit the evolution towards an inflammatory form of COVID-19 thus reducing the risk of hospitalization for severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of SAMHD1-deficient mice has demonstrated that increased DNA damage does not result in higher levels of type I interferon. Instead, the chronic interferon response is driven by the MDA5/MAVS pathway [ 13 ].…”
Section: Discussionmentioning
confidence: 99%